Digital Personal Branding Strategies of Contemporary Preachers on YouTube: A Qualitative Analysis of Gus Miftah and Gus Baha - Astuti, Dyah Rahmi; Enjang, Enjang; Muhtadi, Asep Saeful (Hanifiya: Jurnal Studi Agama-Agama, 2026)
This study explores the construction of personal branding by two prominent Indonesian preachers, Gus Miftah and Gus Baha, through YouTube as a medium for digital Islamic preaching. Employing a qualitative interpretive approach, the research adopts the Circle-P framework, which encompasses five key elements: competency, connectivity, creativity, compliance, and contribution. Data were collected through in-depth interviews, passive participant observation, and content documentation from both da’is’ official YouTube channels. The analysis followed Creswell’s six-step qualitative research method. The findings reveal that personal branding in the digital age is a multidimensional process rooted in each preacher’s unique character, communication style, and social engagement. Gus Miftah constructs his brand by engaging marginalized communities through an inclusive, relaxed, and empathetic style of preaching that breaks conventional boundaries. In contrast, Gus Baha builds his personal branding on scholarly authority, humility, and a calm, narrative approach grounded in Qur’anic interpretation and pesantren traditions. The study concludes that effective personal branding in Islamic preaching is not merely about gaining popularity but about maintaining authenticity, aligning values with audience expectations, and delivering consistent, value-driven communication. This research contributes theoretically to the discourse on Islamic communication and personal branding, and practically offers a strategic model for preachers to enhance their influence and credibility in digital religious spaces.